2015
DOI: 10.3138/jvme.0914-092r1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Veterinary Medical Student Experience: An Institutional Pilot Study

Abstract: Veterinary medical school challenges students academically and personally, and some students report depression and anxiety at rates higher than the general population and other medical students. This study describes changes in veterinary medical student self-esteem (SE) over four years of professional education, attending to differences between high and low SE students and the characteristics specific to low SE veterinary medical students. The study population was students enrolled at the Michigan State Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Although family responsibilities may help explain the gender divide seen in leadership in the profession, one would not expect this to have the same impact on the students’ prior leadership roles (such as in the SU). An additional explanation for the observed gender effect on leadership aspiration may lie in differences in confidence and self‐esteem, observed in this study as well as in another recent report of veterinary students (Miller and others 2015), reports of students in general (Abouserie 1994) and in the population as a whole (Kling and others 1999). The authors found that students of either gender with higher confidence and self‐esteem were more likely to aspire to practice ownership; in the earlier study of self‐esteem in veterinary students, higher self‐esteem students had more positive views of their learning and skills development, and of their educational experience, and experienced less stress, all of which may positively influence their pursuit of leadership roles.…”
Section: Discussionsupporting
confidence: 75%
“…Although family responsibilities may help explain the gender divide seen in leadership in the profession, one would not expect this to have the same impact on the students’ prior leadership roles (such as in the SU). An additional explanation for the observed gender effect on leadership aspiration may lie in differences in confidence and self‐esteem, observed in this study as well as in another recent report of veterinary students (Miller and others 2015), reports of students in general (Abouserie 1994) and in the population as a whole (Kling and others 1999). The authors found that students of either gender with higher confidence and self‐esteem were more likely to aspire to practice ownership; in the earlier study of self‐esteem in veterinary students, higher self‐esteem students had more positive views of their learning and skills development, and of their educational experience, and experienced less stress, all of which may positively influence their pursuit of leadership roles.…”
Section: Discussionsupporting
confidence: 75%
“…Female students had a notably higher median K10 score, a finding consistent with previous studies including the NHS of the general Australian population, practicing veterinarians, and medical students . While there are no studies directly exploring the association between gender and stress levels in veterinary students, some studies report that female students tend to have lower self‐esteem (SE) compared to male students . One study found that students with low SE reported higher levels of stress compared to students with higher SE .…”
Section: Discussionsupporting
confidence: 76%
“…While there are no studies directly exploring the association between gender and stress levels in veterinary students, some studies report that female students tend to have lower self‐esteem (SE) compared to male students . One study found that students with low SE reported higher levels of stress compared to students with higher SE . A US study found that female students also experienced higher levels of depression and anxiety, lower levels of life satisfaction, and lower levels of general health compared to male students .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations